Bacteriological studies on the uterine biopsy and conception rate foil owing treatment in repeat breeding crossbred cows - SHUKLA, S P; SHARMA, R D (The Indian Journal of Animal Reproduction, 2005)
Present study was conducted on 10 normal and 45 repeat breeding crossbred cows. The uteri of normal cows harbouredisolates of E. coli, Staphylococci and Streptococci in 30 percent of the cows. The uteri of 91.12% repeat breeder cows yielded eithersingle or mixed bacterial growth. The organisms isolated were E. coli (18.75%), Corynebacterium (15.64%), Bacilli (14.06%),Staphylococci (12.50%), Pseudomonas (12.50%), and Micrococcus species (3.12%). In vitro drug sensitivity of different isolates ofbacteria varied greatly between the isolates of different genera. Out of a total of 64 isolates recovered from the uterine biopsies84.37, 60.93, 67.18, 42.18, 6.25, 20.31, 29.68, 20.31, 38.12, 20.31 and 9.37 percent were found to be sensitive for gentamycin,chloramphenicol, neomycin, oxytetracycline, ampicillin, chlortetracycline, nalidixic acid, erythromycin, streptomycin, cotrirnoxazoleand furazolidine, respectively. No isolate was found to be sensitive to penicillin. An overall conception rate of 52.96% was achievedin repeat breeders following treatment. Highest conception rate was recorded in animals treated with gentarnycin (72.72%) followedby oxytracycline (62.50%), chlorarnphenicol (40.00%), streptomycin (40.00%) and nalidixic acid (20.00%).
Keywords: Crossbred; repeat breeding; uterine biopsy; bacteriological studies; conception rate